Comparison between Steroid Injections versus Conservative Therapy in the Treatment of Plantar Fasciitis - Tariq, Huzaifa; Ahmad , Rana Dawood; Tariq , Hamza; Mahmood , Tariq; Hassan, A. R.; Mushtaq, Zunair (Indus Journal of Bioscience Research, 2025)
Introduction: Plantar fasciitis can be treated with several approaches as of yet. Common treatments can be divided into non-invasive treatments, such physical therapy (PT), orthosis, oral NSAIDs, radiation therapy (RT) and shock wave (SW) and invasive treatments, such corticosteroid injection (CSI), botulinum toxin injection, platelet-rich plasma (PRP) injection and surgery. So, this study is being undertaken to compare non- invasive conservative methods versus local Steroid injection therapy. The technique with better results will be recommended in future to reduce morbidity of these patients. Materials and Procedures: 434 patients in all fulfilling the inclusion criteria were chosen. Using computer produced random number tables, all of the study participants—who had informed written permission—were randomly divided into two groups. Group B patients received corticosteroid injections; Group A patients underwent conservative treatment. At least four years of post-fellowship experience, a consultant orthopedic surgeon conducted the procedure. Patients had surgery, and following four weeks, fictitious outcomes based on Visual Analogue Scale were observed. Results were assessed as Excellent when VAS was 0; Good when VAS was 0–30mm; Fair when VAS was 30–60mm; Poor when VAS = 60–100mm. Results: In my study, conservative management showed treatment outcome as excellent in 57.60% patients, good in 24.42%, fair in 10.60% and poor in 7.37% patients. While 86.18% of patients receiving corticosteroid injection treatment for Planter Fasciitis had excellent outcome, 6.45% good outcome, 4.15% fair outcome and 3.23 had poor outcome. Conclusion: This study found that treating plantar fasciitis with local corticosteroid injection results in a better functional outcome than with conservative management.